Passivating Surface Defects and Reducing Interface Recombination in CuInS2 Solar Cells by a Facile Solution Treatment. Issue 4 (8th March 2021) - Sood, Mohit; Lomuscio, Alberto; Werner, Florian; Nikolaeva, Aleksandra; Dale, Phillip J.; Melchiorre, Michele; Guillot, Jérôme; Abou-Ras, Daniel; Siebentritt, Susanne
Abstract : Interface recombination at the absorber surface impedes the efficiency of a solar cell with an otherwise excellent absorber. The internal voltage or quasi‐Fermi‐level splitting (qFLs) measures the quality of the absorber. Interface recombination reduces the open‐circuit voltage ( V OC ) with respect to the qFLs. A facile solution‐based sulfur postdeposition treatment (S‐PDT) is explored to passivate the interface of CuInS2 grown under Cu‐rich conditions, which show excellent qFLs values, but much lower V OC s. The absorbers are treated in S‐containing solutions at 80 °C. Absolute calibrated photoluminescence and current–voltage measurements demonstrate a reduction of the deficit between qFLs and V OC by almost one‐third compared with the untreated device. Temperature dependence of the open‐circuit voltage shows increased activation energy for the dominant recombination path, indicating less interface recombination. In addition, capacitance transients reveal the presence of slow metastable defects in the untreated solar cell. The slow response is considerably reduced by the S‐PDT, suggesting passivation of these slow metastable defects. The results demonstrate the effectiveness of solution‐based S‐treatment in passivating defects, presenting a promising strategy to explore and reduce defect states near the interface of chalcogenide semiconductors. Abstract : A solution‐based passivation strategy focusing on near‐surface defects is explored for CuInS2 absorbers grown under Cu‐excess conditions. The impact of near‐surface defects, similar to Cu‐rich selenides, on the device performance is investigated. A model for explaining electrical characteristics is evoked. Results of sulfur‐based treatment using thiourea solution as the sulfur source record an improvement in device performance.